2008
DOI: 10.1097/pcc.0b013e31818c8955
|View full text |Cite
|
Sign up to set email alerts
|

Cranial computed tomographic findings in a large group of children with drowning: Diagnostic, prognostic, and forensic implications*

Abstract: These data from the largest study of CT findings in pediatric drowning clearly illustrate that following submersion injury, intra- or extra-axial bleeding is not seen on cranial CT. Furthermore, an abnormal CT scan at any time was associated with a poor outcome (death or persistent vegetative state). The CT findings and the presenting Glasgow Coma Scale of patients with drowning differ from those of patients who have suffered abusive head trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 23 publications
(23 reference statements)
0
40
0
Order By: Relevance
“…One patient with basilar cistern effacement had a favorable neurologic outcome. Quantitative loss of GWM differentiation measured in HUr was significantly associated with mortality and unfavorable neurologic outcome: death (0.96; HUr, 0.88, 1.07) versus survival (1.14; HUr, 1.1, 1.2) ( p < 0.001) and unfavorable (1.03; HUr, 0.92, 11) versus favorable (1.16; HUr, 1.11, 1.2) ( p < 0.001). Using a cutpoint of 1.2 HUr, the sensitivity of qualitative loss of GWM differentiation for survival was 27% and the specificity was 92%.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…One patient with basilar cistern effacement had a favorable neurologic outcome. Quantitative loss of GWM differentiation measured in HUr was significantly associated with mortality and unfavorable neurologic outcome: death (0.96; HUr, 0.88, 1.07) versus survival (1.14; HUr, 1.1, 1.2) ( p < 0.001) and unfavorable (1.03; HUr, 0.92, 11) versus favorable (1.16; HUr, 1.11, 1.2) ( p < 0.001). Using a cutpoint of 1.2 HUr, the sensitivity of qualitative loss of GWM differentiation for survival was 27% and the specificity was 92%.…”
Section: Resultsmentioning
confidence: 97%
“…Early CT loss of gray-white matter (GWM) differentiation is associated with worse survival and neurologic outcomes following adult OHCA (810). One study of children who suffered drowning, with a small subset having had a cardiac arrest, also demonstrated an association of loss of GWM with worse outcome (11). …”
mentioning
confidence: 99%
“…In reality, however, when cases of known death from hypoxia in infants and children have been reported, subdural hemorrhages were not present [20][21][22]. Many infants who experience episodes of confirmed hypoxia are imaged to determine the extent of brain damage.…”
Section: Introductionmentioning
confidence: 95%
“…A study of paediatric drowning found that all patients with an abnormal initial brain CT died, the most common abnormality being loss of greyewhite differentiation. 12 The main clinical features associated with death or poor neurological outcome are listed in Box 3.…”
Section: Prognosismentioning
confidence: 99%